1982
DOI: 10.1111/j.1095-8649.1982.tb03919.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid status of mullet, Mugil cephalus Linn., exposed to cadmium

Abstract: The effects of acute and chronic cadmium exposures on ascorbic acid concentrations and cadmium accumulation in the tissues of juvenile mullet, Mugil cephalus, are described. Hepatic ascorbic acid reserves were maintained in untreated mullet fed a diet containing ascorbate, but decreased 60% in individuals exposed to 10 mg Cd I-' for six weeks. Ascorbic acid depletion was accompanied by a massive accumulation of cadmium in the liver. Similar changes were found in gill tissue. In contrast, ascorbic acid concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 76 publications
(74 reference statements)
4
35
0
1
Order By: Relevance
“…It was also shown to be rapidly depleted in fish subjected to sublethal levels of organic and inorganic substances (Heath 1995), which was also found in this study after low-dose endosulfan exposure. Thomas et al (1982) reported a 50 % drop in ascorbate levels in hepatic tissue after 6 h of cadmium exposure, and continued exposure resulted in more or less steady depletion. This indicates that ascorbate might have been used up for detoxification processes or for preventing peroxidation of cells (Winston and Diguilo 1991) in endosulphan-exposed fishes.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown to be rapidly depleted in fish subjected to sublethal levels of organic and inorganic substances (Heath 1995), which was also found in this study after low-dose endosulfan exposure. Thomas et al (1982) reported a 50 % drop in ascorbate levels in hepatic tissue after 6 h of cadmium exposure, and continued exposure resulted in more or less steady depletion. This indicates that ascorbate might have been used up for detoxification processes or for preventing peroxidation of cells (Winston and Diguilo 1991) in endosulphan-exposed fishes.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of ascorbic acid in fish have been discussed in the context of nutritional conditions and are concerned with vitamin C deficiency (Halver et al 1975), an adverse effect due to exposure to toxicants (Mayer et al 1978, Thomas et al 1982, Yamamoto & Inoue 1985 or in relation to physiological stress (Wedemeyer 1969). However, there are no published records how harsh environmental conditions and scarcity of food may affect ascorbic acid metabolism.…”
Section: Introductionmentioning
confidence: 98%
“…Our results of crystallized ascorbic acid concentration in AA and AAL diets were similar to the results obtained by Marchetti and Tossani (1999) and Volker and Fenster (1994) who concluded that the loss of crystalline ascorbic acid in pelleted feed during 12 weeks of storage was 44% and 54%, respectively. Ascorbic acid liver content is usually considered an indicator of the vitamin C status (Gabaudan et al, 1991;Sandnes and Waagbø, 1991;White et al, 1993) and has been described as a physiological indicator of stress (Wedemeyer and Yasutake 1977;Wedemeyer and McLeay, 1981;Thomas et al, 1982;Thomas, 1990). Also, because of the role that vitamin C apparently plays in the synthesis of corticosteroids (Sauberlich, 1984), feeding high levels of vitamin C has been proposed as beneficial in reducing the effects of physiological stress in fish (Jaffa, 1989;Hardie et al, 1991) and chickens (Brake et al, 1992;Pardue and Williams, 1992).…”
Section: Discussionmentioning
confidence: 99%